1982
DOI: 10.1017/s002202990002255x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen on the keeping quality of milk: I. Oxidized flavour development and oxygen uptake in milk in relation to oxygen availability

Abstract: Oxidized flavour developed in whole milk only through the catalytic effect of either Cu or light. The O 2 requirement for the 2 processes differed as did the characteristics of the off-flavours produced. Cu-induced oxidized flavour was described as 'cardboardy' and light-induced oxidized flavour was 'painty'. Light-induced oxidized flavour increased in intensity with O 2 loss, and could be prevented in stored milk by restricting access of O 2 . In UHT milk with a dissolved O 2 content of 66 mg/1, and in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The white (TiO 2 ) pigmented bottles were chosen on the basis of consumer preference (White, 1985) with regard to colour and their potential protective effect against harmful incident light. The carbon black pigment has been suggested (Schro¨der, 1982) for maximum protection against UV-VIS radiation, with both pigments being approved by the Food and Drug Administration, USA. Bottle (4) containing inner and outer white coloured layers was white in colour.…”
Section: Packaging Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The white (TiO 2 ) pigmented bottles were chosen on the basis of consumer preference (White, 1985) with regard to colour and their potential protective effect against harmful incident light. The carbon black pigment has been suggested (Schro¨der, 1982) for maximum protection against UV-VIS radiation, with both pigments being approved by the Food and Drug Administration, USA. Bottle (4) containing inner and outer white coloured layers was white in colour.…”
Section: Packaging Materialsmentioning
confidence: 99%
“…Part of the explanation for this may be the relatively large HS (containing air) which was similar in all packages (50-60 mL). Schro¨der (1982) reported that even a small HS in a container provides a considerable O 2 reservoir relative to the quantity dissolved in milk. In a container with a 15% HS (a common proportion for a commercial milk carton), the ratio between dissolved and gaseous O 2 in milk at 10 1C is approximately 1:5.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is now generally well recognized, but even recently indirect contamination has been found through residues of cleaning/disinfectant solutions in processing plants (Van Duin, 1974), or corrosive water which dissolved copper out of water heaters (Bertelsen & Narlid, 1978). Schroder (1982a) found that Cu 2+ -induced oxidized flavour was not directly related to the O 2 concentration of Cu 2+ -adulterated pasteurized milk. Although complete deoxygenation prevented formation of the off flavour, partial deoxygenation produced a greater intensity of off flavour than no deoxygenation.…”
Section: Copper-induced Lipid Oxidationmentioning
confidence: 86%
“…Since xanthine oxidase is abundant in the MFGMs, it is possible that initiation of lipid peroxidation could be caused by this enzyme (McPherson and Kitchen 1983). It is also important to note that milk normally becomes saturated with 0, between milking and processing, and that this oxygen is not subsequently removed (Schroder 1982).…”
Section: Introductionmentioning
confidence: 99%